Generation of micro(nano)plastics and migration of plastic additives from Poly(vinyl chloride) in water under radiation-free ambient conditions. (July 2022) - Qin, Junhao; Zeng, Shuqing; Wang, Xi; Lin, Chuxia
Abstract: A batch experiment was conducted to observe the liberation of micro- and nano-sized plastic particles and plastic additive-originated organic compounds from poly(vinyl chloride) under radiation-free ambient conditions. The weathering of PVC films in deionized water resulted in isolated pockets of surface erosion. Additional ● OH from Fenton reaction enhanced PVC degradation and caused cavity erosion. The detachment of plastic fragments from the PVC film surfaces was driven by autocatalyzed oxidative degradation. Over 90% of micro-sized plastic particles were <60 μm in length. The detached plastic fragments underwent intensified weathering, which involved strong dehydrochlorination and oxidative degradation. Further fragmentation of micro-sized particles into nano-sized particles was driven by oxidative degradation with complete dehydrochlorination being achieved following formation of nanoplastics. 20 organic compounds released from the PVC films into the solutions were identified. And some of them can be clearly linked to common plastic additives. In the presence of additional ● OH, the coarser nanoplastic particles (>500 nm) tended to be rapidly disintegrated into finer plastic particles (<500 nm), while the finest fraction of nanoplastics (<100 nm) could be completely decomposed and disappeared from the filtrates. The micro(nano)plastics generated from the PVC weathering were highly irregular in shape. Graphical abstract: Image 1 Highlights: PVC weathering in water only resulted in isolated pockets of surface erosion. Fragmentation of microplastics into nanoplastics is driven by oxidative degradation. A range of compounds related to plastic additives were detected. ● OH caused rapid disintegration of coarser nanoplastics into finer nanoplastics Finest nanoplastics (<100 nm) could be completely decomposed by . ● OH